Democracy of Pakistan and Dilemma of Liberalism under Constant Struggle with Religious Nationalism and Politicized Institutions - Dr. Fauzia Ghani (Journal of Political Studies, 2020)
Democracy in 21st century is challenged with valiant contemporary issues of globalization, terrorism, media and information revolution. Due to these issues, today’s democracy has been amalgamated with threats of authoritarianism, military coup d’état, extremism, terrorism, liberalism, and right activist movements which have constantly tried to weakened down the framework of democratic policies in any country. This research article has focused on the objective of constant struggle of Pakistan with a focus on current governmental regime and its liberal policies in order to steer the wheel of country towards true democracy. The methodology of paper is descriptive and qualitative in nature in which dependent variable of Pakistan’s democracy has been analyzed with the independent variables of religious and politicized institutions which are acting as hurdle in attaining sustained democratic system in the country, whereas dilemma of liberalism is acting as an intervening variable in between these. The relationship between the right wing movements, including the religion based nationalism dilemma will be analyzed in order to know its influence whether it can work as a supplement for a better democratic future of Pakistan or will create more hurdles in it.